A MULTICENTER REVIEW EVALUATING THE RISK OF RHEGMATOGENOUS RETINAL DETACHMENT POST ENDOPHTHALMITIS: A Canadian Retina Research Network Investigation. Issue 8 (August 2022) - Nanji, Keean; Kherani, Imaan; Khan, Mohammad; Williams, Geoff; Muni, Rajeev H.; Chaudhary, Varun; Kherani, Amin
Abstract : Supplemental Digital Content is Available in the Text. A 10-year multicenter review of 316 consecutive patients diagnosed with endophthalmitis. Endophthalmitis etiology, management, and prognosis are reviewed. The 32 cases further complicated by rhegmatogenous retinal detachment are described. Predictors of retinal detachment post endophthalmitis are explored through regression analysis. Abstract : Purpose: To describe the characteristics of rhegmatogenous retinal detachments (RDs) that developed after endophthalmitis and to provide insight regarding incidence, management, and outcomes. Methods: Retrospective chart review of consecutive patients diagnosed with endophthalmitis at two Canadian institutions and from one surgeon at a third center over a 10-year period. Results: Three hundred sixteen eyes presented with endophthalmitis of which 32 (10%) were complicated by subsequent RD. The mean age (SD) of patients was 72.0 (13.77) years. Intravitreal injections (33%) and cataract surgery (31%) were the most common inciting events for the endophthalmitis. Cases were managed with tap and inject (16%), vitrectomy (30%), or both (47%). There were no differences in the rate of RD when comparing the inciting events, microbial growth, or management approaches. Baseline visual acuity was the only predictor of RD ( P = 0.009). There was an improvement in visual acuity following management of the RD (logarithm of the minimum angle of resolution 2.33 vs. 1.69 or Snellen hand motion vs. 20/980, P = 0.009), but final visual acuity in these patients was worse than in those who did not develop RD (logarithm of the minimum angle of resolution 1.69 vs. 1.27 or Snellen 20/980 vs. 20/372, P = 0.029). Conclusion: All patients with RD post endophthalmitis required additional surgery, and functional outcomes remained poor. Nevertheless, repair of these RDs can preserve some vision and be globe saving.